2021
DOI: 10.1155/2021/8861841
|View full text |Cite
|
Sign up to set email alerts
|

What Factors Contribute to Higher Travel Happiness? Evidence from Beijing, China

Abstract: Travel happiness has drawn increasing attention in recent years. However, the empirical research in developing countries’ context is very limited, and few studies consider both cognitive and affective evaluations during traveling. This study uses web-based survey data collected in Beijing, China, and applies multiple regression analysis to examine impacts of sociodemographic attributes, travel characteristics, residential environment, mode consonance, self-evaluation, and health conditions, on travel happiness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
(65 reference statements)
0
4
0
Order By: Relevance
“…The results are consistent and encouraging. While the oldest article used specific aspects of satisfaction (St-Louis et al, 2014 ) to operationalise travel satisfaction, the other five studies used some variant of the Satisfaction with Travel Scale (Friman et al, 2017 ; Smith, 2017 ; Singleton, 2019 ; Fan et al, 2021 ; Liu et al, 2021 ). These studies showed a significant positive correlation between walking and cycling and travel satisfaction.…”
Section: Resultsmentioning
confidence: 99%
“…The results are consistent and encouraging. While the oldest article used specific aspects of satisfaction (St-Louis et al, 2014 ) to operationalise travel satisfaction, the other five studies used some variant of the Satisfaction with Travel Scale (Friman et al, 2017 ; Smith, 2017 ; Singleton, 2019 ; Fan et al, 2021 ; Liu et al, 2021 ). These studies showed a significant positive correlation between walking and cycling and travel satisfaction.…”
Section: Resultsmentioning
confidence: 99%
“…Lunke ( 40 ) further conducted a study on the satisfaction of traveling by different modes of public transport and found that commuting by train and metro was more satisfying than commuting by bus or tram. For active travel modes, walking appears more satisfying than non-motorized trips; when using motorized vehicles, company shuttle commuting is preferred, followed by car ( 12 , 14 ). Yet another study stated that there is no significant correlation between travel mode and travel satisfaction ( 15 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although a considerable number of scholars have worked on analyzing the factors influencing travel satisfaction, including travel mode ( 11 , 12 ), travel time ( 13 , 14 ), travel purpose ( 15 ), built environment (accessibility, density, convenience) ( 16–18 ), these were conducted in urban areas, and there is a paucity of research on rural travel satisfaction. Moreover, roads serve as a bridge connecting rural residents with their often frequented markets, and the quality of roads and their ancillary facilities are an important factor affecting the satisfaction of rural residents ( 19 , 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…They suffer from low connections during modal shifts, long commute duration, less-developed transition and transport conditions (road congestion, public transport crowdedness, etc.) (Fan et al, 2021).…”
Section: Introductionmentioning
confidence: 99%